Multi-omics techniques revealing the mechanism of Polygonatum sibiricum Huangjiu in alleviating hyperlipidemia in mice - Geng, Jingzhang; Zhang, Guotai; Dong, Jianwei; Tian, Honglei; Lou, Zaixiang (Frontiers in Nutrition, 2025)
IntroductionHyperlipidemia poses a serious threat to human health. However, given the significant adverse effect of drug therapy, finding safe and efficient lipid-lowering agents has become a focal point of interest. Polygonatum sibiricum Huangjiu (PSHJ) is hypothesized to exert lipid-lowering effects. This study examined PSHJ’s ability to alleviate hyperlipidemia in mice caused by a high-fat diet, and the regulatory mechanism was studied via gut microbiome and fecal lipidomics.MethodsA mouse model of hyperlipidemia was established using a high-fat diet. The experimental groups were administered PSHJ, and serum lipid profiles—including triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C)—were measured. Histopathological examinations of the liver, kidney, and small intestine were performed to assess tissue damage. The gut microbiota composition was analyzed to evaluate diversity and the abundance of short-chain fatty acids (SCFAs)-producing bacteria. Fecal lipidomics was employed to investigate alterations in lipid metabolic pathways.ResultsPSHJ treatment significantly increased HDL-C levels while reducing serum TG, TC, and LDL-C levels in hyperlipidemic mice. Histological analysis revealed that PSHJ alleviated damage in the liver, kidney, and small intestine. Furthermore, PSHJ enhanced gut microbial diversity and promoted the proliferation of SCFA-producing bacteria, leading to elevated SCFA levels. Lipidomic analysis indicated that PSHJ modulated metabolic pathways related to glycerophospholipids, glycerolipids, and fatty acids, thereby facilitating the breakdown of TG and diacylglycerol (DG).DiscussionThe findings suggest that polysaccharides in PSHJ function as prebiotics, enriching beneficial gut microbiota and increasing SCFA production. These SCFAs, along with polysaccharides, appear to regulate key lipid metabolic pathways, enhancing the degradation of TG and DG. This study shows that PSHJ has active components that can alleviate hyperlipidemia, thereby laying a theoretical foundation for extracting bioactive substances from Huangjiu for future medical or dietary use.